Pemanfaatan limbah kolam lele (clarias sp.) Sebagai pupuk organik dalam penerapan akuaponik - Dimas Galang Prakosa (Samakia : Jurnal Ilmu Perikanan, 2021)
The aims of this study was to determine the effect of the aquaponic system on the normalization of water quality for organic catfish cultivation, the survival rate of catfish and the growth of water spinach in the aquaponics system. The research method to be carried out is an experimental method using a completely randomized design (CRD) with different stocking densities, namely P1 (100 fish/m2), P2 (250 fish/m2), and P3 (500 fish/m2). The parameters measured were the water quality of the catfish culture media including NH3, NO2, NO3, pH, and dissolved oxygen, as well as the survival rate of catfish and kale plant growth (plant height, number of leaves, and leaf width). The results showed that rearing catfish with an aquaponic system with Kangkung plants could stabilize water quality. Value of water quality NH3 (0 – 0.1 ppm), NO2 (0 – 0.881 ppm), NO3 (0 – 1.443 ppm), pH (6 – 7.8), and dissolved oxygen (4.5 – 6.2 ppm). The survival rate was P1 (95.2%), P2 (94.3%), P3 (89.6%). The best growth of kale was found in the P3 treatment, namely plant height 37.2 cm, leaf width 2.5 cm, and number of leaves 24 strands. The results showed that the water quality was relatively stable. The higher the stocking rate, the lower the survival rate of catfish, on the other hand, the higher the stocking density, the better the growth of kale plants.